THE ROLE OF SOCIAL MEDIA MARKETING AND BRAND MANAGEMENT IN GLOBAL MARKETING - Tangatarova Shahrizada (Sciental Journals Publishing, 2025)
In the age of globalization, businesses strive to establish strong brand identities and connect with consumers across borders. Social media marketing and brand management have become central to these efforts. This paper explores the interconnected roles of social media marketing and brand management in global marketing strategies. It examines how companies use social media platforms to build, manage, and sustain brand equity while engaging with international audiences. The study reviews relevant literature and presents a critical analysis of how these tools drive consumer loyalty, cultural adaptation, and market penetration. The paper concludes with insights and recommendations for businesses aiming to enhance their global presence.
Keywords: Social media marketing; brand management; global marketing strategies; consumers; cultures; social media analytics; companies; marketing process.